مهارة الاستماع و طرق تنميتها عند المتعلم - بوقنين, سهام (كلية الأدب العربي والفنون, 2024)
تهدف الدراسة المعنونة ب : " مهارة الاستماع و طرق تنميتها عند المتعلم – المرحلة الابتدائية أنموذجاً – " إلى الوقوف على طرق تدريس مهارة الاستماع و دورها في تنمية الحصيلة اللغوية للمتعلم ، و لمعرفة واقع تدريسها و لمعرفة العوامل المؤثرة في تعليمها ، و للوقوف على المعوقات و المشاكل التي تعرقل عملية الاستماع . فمهارة الاستماع هي عملية يركز فيها المستمع على كلام المتحدث بهدف التعرف على المعلومات أو المشاعر التي يريد إيصالها . و تعتبر مهارة الاستماع مهارة أساسية و مهمة بين المهارات اللغوية الأخرى التحدّث و القراءة و الكتابة . فالاستماع عملية من عمليات التواصل و الاتصال اللغوي بين البشر و عن طريقه يتم الكلام أو الإشارة أو اللغة الجسدية للكلمات ، و تساعد على تحسين الفهم و التواصل و التفاعل مع الآخرين ، و تؤدي إلى توسيع الثروة اللغوية للمتعلم لما يسمعه من مفردات لغوية متنوعة . و قد اقتضت هذه الدراسة تقسيم الموضوع إلى : مقدمة و مدخل و فصلين نظريين و فصل تطبيقي و خاتمة ، متبعتا المنهج الوصفي التّحليلي ، و استعملت الاستبيان كأداة للبحث في الدراسة الميدانية The study entiled : " The listening skill and methods for developing it among the learner – the primary stage as model " aims to examine the methods of teaching the listening skill and its role in developing the learner’s linguistic vocabulary , to know the reality of teaching it , to know the factors influencing its teaching , and identify the obstacles and problems that hinder the listening process . Listening skill is a process in which the listener focuses on the speaker’s words with the aim of identifying the information or feelings he wants to convey. The listening skill is considered a basic and important skill among the other linguistic skills of speaking , reading and writing . Listening is a process of communication between humans through which words are spoken , gestured , or in physical language . It help improve understanding , communication, and interaction with others , and leads to expanding the learner’s linguistic wealth for the diverse linguistic vocabulary he hears . This study required diving the topic into : an introduction , entrance , two theoretical chapters , an applied chapter , and a conclusion , following the descriptive and analytical approach , and used the questionnaire as a research tool in the field study .
المرحلة الابتدائية أنموذجا
Keywords: العملية التعليمية – التعليم - التعلم – المعلم – المتعلم – المادة التعليمية – مثلث التعليمية - المهارة – المهارات اللغوية - مهارة الاستماع – المرحلة الابتدائية; Educational process – education - learning – the teacher – learner – educational material – educational triangle – skill- listening skill – primary stage .